Regulation of epidermal barrier function and pathogenesis of psoriasis by serine protease inhibitors - Wang, Juanjuan; Li, Junqin; Zhou, Ling; Hou, Hui; Zhang, Kaiming (Frontiers in Immunology, 2024)
Serine protease inhibitors (Serpins) are a protein superfamily of protease inhibitors that are thought to play a role in the regulation of inflammation, immunity, tumorigenesis, coagulation, blood pressure and cancer metastasis. Serpins is enriched in the skin and play a vital role in modulating the epidermal barrier and maintaining skin homeostasis. Psoriasis is a chronic inflammatory immune-mediated skin disease. At present, most serpins focus on the pathogenesis of psoriasis vulgaris. Only a small number, such as the mutation of SerpinA1/A3/B3, are involved in the pathogenesis of GPP. SerpinA12 and SerpinG1 are significantly elevated in the serum of patients with psoriatic arthritis, but their specific mechanism of action in psoriatic arthritis has not been reported. Some Serpins, including SerpinA12, SerpinB2/B3/B7, play multiple roles in skin barrier function and pathogenesis of psoriasis. The decrease in the expression of SerpinA12, SerpinB7 deficiency and increase in expression of SerpinB3/4 in the skin can promote inflammation and poor differentiation of keratinocyte, with damaged skin barrier. Pso p27, derived from SerpinB3/B4, is an autoantigen that can enhance immune response in psoriasis. SerpinB2 plays a role in maintaining epidermal barrier integrity and inhibiting keratinocyte proliferation. Here we briefly introduce the structure, functional characteristics, expression and distribution of serpins in skin and focus on the regulation of serpins in the epidermal barrier function and the pathogenic role of serpins in psoriasis.